Design and Preparation of a Self-Inhaling Internal Cooling Grinding Wheel with a Leaf Order Arrangement Structure - Zixuan Wang; Zhengyu Sun; Yinhao Huang; Tianbiao Yu; Jun Zhao (Applied Sciences)
Grinding wheels are important tools for precision machining. Traditional grinding wheels have issues such as high grinding forces and temperatures on the machined surface, and excessive use of grinding fluids often leads to significant waste. To solve such problems, this paper proposes a self-inhaling internal cooling structured grinding wheel with a leaf order arrangement based on laser cladding technology, by which the “air barrier effect” in grinding is avoided. In this study, the structure of the grinding wheel substrate, as well as the arrangement of abrasive grain clusters, were optimized. The internal flow field and grinding zone flow field of the grinding wheel were simulated using the computational fluid dynamics method. To ensure stable grinding performance, the effects of different cooling hole positions and sizes on fluid motion were revealed, and the influence of grinding wheel rotational speed and coolant pressure on outlet velocity were analyzed. The results show that uniform coolant outlet velocity distribution can be achieved via matching the grinding wheel’s rotational speed with the initial pressure of the cooling fluid inside the grinding wheel. This study further explored the fluid motion patterns in the grinding zone for four differently structured surfaces. The advantages of using leaf order theory to arrange abrasive clusters were verified. Additionally, orthogonal experiments and range analysis were conducted to study the laser cladding preparation process of grinding wheels. With the optimal process parameters, a self-inhaling internal cooling grinding wheel with a leaf order arrangement structure was fabricated.